The Effectiveness of Nutritional Counseling Media in Gout Patients - afriyana siregar; Adelia Dwi Putri; Yulianto Yulianto; Susyani Susyani; Muzakar Muzakar (jitek, 2026)
To enhance public awareness in adopting a healthier lifestyle, it is essential to provide support and information through nutritional counseling. This approach allows for the development and application of knowledge in daily life. The objective of this study is to evaluate the effectiveness of nutrition counseling using booklets and videos on knowledge, nutrient intake, purine intake, and uric acid levels in gout patients. The research method employed is an experimental design with a pre-experimental two-group pre-test post test design. The study sample consists of gout patients residing in the Social Health Center (Puskesmas Sosial) Palembang area, with purposive sampling used to select a total of 40 gout patients divided into 2 groups. Each group, whether receiving booklets or videos, was given 2 counseling sessions per week for 4 weeks. An analysis was conducted to compare changes in knowledge, nutrient intake, purine intake, and uric acid levels before and after the intervention. For data with normal distribution, a paired samples t test was applied, whereas non-normally distributed data were assessed using the Wilcoxon signed-rank test. The findings demonstrated that nutrition counseling delivered through booklet and video media significantly improved participants’ knowledge, purine intake, and uric acid levels (p < 0.05). In contrast, no statistically significant change was observed in overall nutrient intake (p > 0.05).